Assessment of the pollen diet in a wood-dwelling augochlorine bee (Halictidae) using different approaches - Dalmazzo, Maria de Los Milagros (2014)
Most studies on bee pollen diet are based on the abundance of each pollen type composing honey or pollen stores of whole nests (pollen counts). In an effort to characterize the diet of the augochlorine bee Augochlora amphitrite, we employed nest and intra-nest pollen analyses and bee flower visitation. In addition, we tested a novel approach, the Index of Relative Importance (IRI), a method that combines pollen counts, pollen volume and frequency of pollen occurrence. Using nest pollen analysis we found that the Ludwigia type dominated pollen counts, comprising 56% of whole nests, and thus would have concluded that this is the only most important pollen source in the diet. Instead we found seven other important sources including Ipomoea alba, I. cairica, Gymnocoronis spilanthoides and Pavonia types as well as 26 new floral hosts using all four methods in combination. Thus, we recommend that other studies of bee diet include these other approaches when possible, and especially the novel approach of IRI.